Full-scale testing and foundation design : honoring Bengt H. Fellenius - Hussein, Mohamad H.; Fellenius, Bengt H.; American Society of Civil Engineers. Geo-Institute. (Reston, Va. : American Society of Civil Engineers)
"Publications by Bengt H. Fellinius": p. xi-xxvi.